2020
DOI: 10.1002/solr.202000292
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Perovskite Solar Modules with Functional Layers Fully Vacuum Deposited

Abstract: Large‐area homogeneous and uniform perovskite films are key to the mass production of perovskite solar cells, especially the flexible ones. Different from the solution‐processed preparation, herein an all‐evaporation technique is developed for both perovskite films and the hole‐transporting layer in the modules. With the two‐step strategy of active‐layer design, homogeneous large‐area perovskite films are prepared via evaporation of first PbI2 and then CH3NH3I. An 2,3,5,6‐tetrafluoro‐7,7,8,8‐tetracyanoquinodime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…A vacuum deposition process has recently released notable results despite a limited number of groups being involved in the previous studies. [ 54,72,73 ] A large PSM based on the thermally co‐deposition of MAI and PbI 2 demonstrated 18.13% of PCE (area = 21 cm 2 ), showing only 10% difference in PCE compared with the unit cell (20.28% of PCE with 0.16 cm 2 ). [ 54 ] Furthermore, the vacuum process allows a flexible substrate to be easily adopted owing to the low temperature process.…”
Section: High Volume Manufacturing Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…A vacuum deposition process has recently released notable results despite a limited number of groups being involved in the previous studies. [ 54,72,73 ] A large PSM based on the thermally co‐deposition of MAI and PbI 2 demonstrated 18.13% of PCE (area = 21 cm 2 ), showing only 10% difference in PCE compared with the unit cell (20.28% of PCE with 0.16 cm 2 ). [ 54 ] Furthermore, the vacuum process allows a flexible substrate to be easily adopted owing to the low temperature process.…”
Section: High Volume Manufacturing Technologymentioning
confidence: 99%
“…The flexible PSM showed a 13.15% of PCE (area = 16 cm 2 ), which was comparable to that of the rigid substrate, 15.06%. [ 72 ] The HCVD method enables the vapor of organic precursors to be easily controlled during CVD by separate optimization either in tube furnace or vacuum oven. A mixed composition of Cs 0.1 FA 0.9 PbI 2.9 Br 0.1 via HCVD demonstrated a comparably lower PCE of 13.3% from a 0.09 cm 2 ‐sized unit cell due to a negative impact of a vacuum annealing process on underlying SnO 2 layer during the HCVD, [ 61 ] which was more enhanced by adopting RHCVD coupled with a systematic optimization, leading to a PCE of 15.5%.…”
Section: High Volume Manufacturing Technologymentioning
confidence: 99%
“…All evaporated PVK devices achieved a champion PCE of 15.06% at 16 cm 2 active area. 102 By optimizing the evaporation process parameters such as deposition rate, substrate temperature, chamber pressure, etc., PCEs of more than 20% have recently been reported with co-evaporated PVK layers. 103 Moreover, 18.13% PCE of a 21 cm 2 PVK module by coevaporation method was reported.…”
Section: Solution and Evaporation Process For Large-scale Pvk Layermentioning
confidence: 99%
“…Lei et al first formed a PbI 2 layer by normal evaporation and then fabricated MAI by flash evaporation to obtain a homogeneous large‐scale PVK film. All evaporated PVK devices achieved a champion PCE of 15.06% at 16 cm 2 active area 102 . By optimizing the evaporation process parameters such as deposition rate, substrate temperature, chamber pressure, etc., PCEs of more than 20% have recently been reported with co‐evaporated PVK layers 103 .…”
Section: Solution and Evaporation Process For Large‐scale Pvk Layer Dmentioning
confidence: 99%
“…Lei et al demonstrated a two-step flash-evaporation method where PbI 2 films and MAI films were flash evaporated consecutively to obtain homogeneous large-area perovskite films. [143] With the virtue of this method, they fabricated inverted fPSC module with active area of 16.0 cm 2 and achieved PCE over 13 %. Solution processability and high band gap (~1.6 eV) of perovskites make it suitable for the absorber layer of the top cell in a tandem configuration.…”
Section: Perovskite Layermentioning
confidence: 99%